Lowered insulin signalling ameliorates age-related sleep fragmentation in Drosophila. - Athanasios Metaxakis; Luke S Tain; Sebastian Grönke; Oliver Hendrich; Yvonne Hinze; Ulrike Birras; Linda Partridge (PLoS Biology)
Sleep fragmentation, particularly reduced and interrupted night sleep, impairs the quality of life of older people. Strikingly similar declines in sleep quality are seen during ageing in laboratory animals, including the fruit fly Drosophila. We investigated whether reduced activity of the nutrient- and stress-sensing insulin/insulin-like growth factor (IIS)/TOR signalling network, which ameliorates ageing in diverse organisms, could rescue the sleep fragmentation of ageing Drosophila. Lowered IIS/TOR network activity improved sleep quality, with increased night sleep and day activity and reduced sleep fragmentation. Reduced TOR activity, even when started for the first time late in life, improved sleep quality. The effects of reduced IIS/TOR network activity on day and night phenotypes were mediated through distinct mechanisms: Day activity was induced by adipokinetic hormone, dFOXO, and enhanced octopaminergic signalling. In contrast, night sleep duration and consolidation were dependent on reduced S6K and dopaminergic signalling. Our findings highlight the importance of different IIS/TOR components as potential therapeutic targets for pharmacological treatment of age-related sleep fragmentation in humans.